2008
DOI: 10.1007/s11356-008-0018-z
|View full text |Cite
|
Sign up to set email alerts
|

The zebrafish embryo model in environmental risk assessment—applications beyond acute toxicity testing

Abstract: Challenges for future research are (1) the identification of further suitable molecular markers as indicators of the mode of action, (2) the establishment of strong links between (molecular) effects in short-term assays in embryos and long-term (toxic) effects on individuals, (3) the definition of limitations of the model and (4) the development of tests that can be used for regulatory purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
258
0
47

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 518 publications
(310 citation statements)
references
References 77 publications
5
258
0
47
Order By: Relevance
“…Our study confirmed that zebra fish eggs and embryos could become a valuable model for assessing the risks of chemical substances in the environment due possibly achieving a cheap and precise analysis at a reduced scale, being also an alternative for the adult zebra fish acute tests [12,17,[28][29][30][31].…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Our study confirmed that zebra fish eggs and embryos could become a valuable model for assessing the risks of chemical substances in the environment due possibly achieving a cheap and precise analysis at a reduced scale, being also an alternative for the adult zebra fish acute tests [12,17,[28][29][30][31].…”
Section: Discussionsupporting
confidence: 64%
“…Zebra fish embryos are complete organisms that allow their use as alternatives in acute fish tests for diverse effluent testing [12,[21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Within the last decade, increasingly, attempts were made to improve EDA approaches, e.g., by including fractionation methods for more polar compounds (Lubcke-von Varel et al 2008;Meinert et al 2007), methods for addressing the bioavailability within the fractionation approach Schwab and Brack 2007), incorporating structure generation and mass spectral classifiers for identifying of unknown substances (Schymanski et al 2008), and the use of additional biological endpoints, such as gene expression alterations (Scholz et al 2008), teratogenicity, and genotoxicity (Kosmehl et al 2007), and steroidogenesis (Hecker et al 2007). One particular topic that has concerned risk assessors and regulator during the past two decades is the issue of endocrine disruption.…”
Section: Current Eda Approaches and Their Limitationsmentioning
confidence: 99%
“…Zebrafish embryos/larvae are an ideal model for assessing developmental neurotoxicity associated with toxicant exposure (Scholz et al, 2008). In the present study, the expression levels of several genes involved in central nervous system development were examined, and growth of spinal motoneuron axons was measured in zebrafish larvae, as it has been shown that exposure to PBDEs or Pb can impair axon growth (Kodavanti and CurrasCollazo, 2010;Lee and Freeeman, 2014).…”
Section: Introductionmentioning
confidence: 99%